The Problems and Peculiarities of Modelling Integrated Systems of Heterogeneous Traffic Services - Oleg Ja, Kravets; Oleg N., Choporov (Journal of Siberian Federal University. Mathematics & Physics, 2018)
The article considers some problems and peculiarities of the modelling and rational design of heterogeneous traffic servicing integrated systems. The aim of the article is to undertake a comparative analysis of existing technologies in modelling distributed systems with a heterogeneous medium as part of a sub-system of managing the modelling and upgrading of the systems in question. The research subject is a system consisting of air and cable multiple-access systems. The authors have used the methodology of conceptual and mathematical modelling within the queuing systems theory. The article presents a model of heterogeneous subsystem representation, assigns the optimal task for choosing the multicriteria of a system building variants, and proposes integrated protocols for the functioning of the system as well as a mathematical model based on z-transferring of delivery time and the service interval distribution series. The obtained results can be used for the reconfiguration of both static and dynamic heterogeneous (according to the transmission medium) information systems.